PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE (TPSQ) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS IX SMP NEGERI 22 PADANG - Sergia, Yana; Harisman, Yulyanti (Jurnal Edukasi dan Penelitian Matematika, 2024)
- The ability to communicate mathematical concepts effectively is an important part of mastering mathematical concepts. Unfortunately, the mathematical communication skills of students in grade IX of SMPN 22 Padang are still lacking. To overcome this obstacle, we used the Think Pair Square learning model. A quasi-experimental design, consisting of a non-equivalent control group used only after the exam, was used in this study. A p-value of 0.002 was shown in the t-test analysis, which is smaller than the significance level of 0.05. The results of grade IX students at SMPN 22 Padang who used the TPSQ learning model to improve their mathematical communication skills were better than students who used the direct learning model.Keywords–Mathematical Communication Skills, Think Pair Square, Direct Learning